Użyteczność międzynarodowego modelu wyceny aktywów kapitałowych (International CAPM) w szacowaniu kosztu kapitału własnego - Zarzecki, Dariusz (Usefulness of International CAPM in Estimating Cost of Equity, 2006)
Estimation of a cost of equity for international markets is a developing area of theory and practice. The concept of the capital asset pricing model (CAPM) can be applied to the international market. To do so, the CAPM has to be converted to a country-specific international format. The risk-free rate and beta are specific to the country being analyzed and the equity risk premium is calculated on a worldwide basis. Beta should be estimated using the world equity market as the market benchmark. The concept seems to be interesting and attractive but application is more complicated and difficult.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 747-752